Digital Literacy in Action: An Ethnographic Study of EFL Classrooms in Indonesian Senior High School - Mahmud, Adi F.; Mahmud, Murni; Weda, Sukardi; Munir (Universitas Sulawesi Barat, 2025)
This ethnographic study investigates the integration of digital literacy in EFL classrooms in an Indonesian senior high school. Although digital literacy is essential in contemporary Education, research in rural or under-resourced environments is scarce, especially on its cultural and pedagogical aspects. The study employed a qualitative ethnographic methodology, conducted over six months at SMA Negeri 10 Kota Ternate, which incorporated participant observation, semi-structured interviews, document analysis, and field notes. The findings indicated that Education based on digital literacy was executed in three fundamental phases: planning, implementation, and evaluation. Educators incorporated available digital resources, such as YouTube, Canva, Google Forms, and Kahoot, to create engaging and interactive learning environments. Nonetheless, infrastructure limitations and varied levels of digital proficiency posed ongoing obstacles. Three emerging cultural themes—pedagogical adaptation, negotiated involvement, and reflective assessment—highlighted how educators tailored digital practices to their sociocultural setting. The study suggests that digital literacy in EFL education is both a technical process and a contextual social practice, influenced by factors such as context, agency, and resource availability. It advocates for improved teacher professional development and infrastructure to facilitate equitable and contextually relevant digital instruction in marginalised educational environments.